Impact of COVID-19-related public containment measures on the ST elevation myocardial infarction epidemic in Belgium: a nationwide, serial, cross-sectional study. Issue 8 (10th November 2021) - Claeys, Marc J.; Argacha, Jean-François; Collart, Philippe; Carlier, Marc; Van Caenegem, Olivier; Sinnaeve, Peter R.; Desmet, Walter; Dubois, Philippe; Stammen, Francis; Gevaert, Sofie; Pourbaix, Suzanne; Coussement, Patrick; et al.
Abstract: Aims: The current study assessed the impact of COVID-19-related public containment measures (i.e. lockdown) on the ST elevation myocardial infarction (STEMI) epidemic in Belgium. Methods and results: Clinical characteristics, reperfusion therapy modalities, COVID-19 status and in-hospital mortality of consecutive STEMI patients who were admitted to Belgian hospitals for percutaneous coronary intervention (PCI) were recorded during a three-week period starting at the beginning of the lockdown period on 13 March 2020. Similar data were collected for the same time period for 2017–2019. An evaluation of air quality revealed a 32% decrease in ambient NO2 concentrations during lockdown (19.5 µg/m³ versus 13.2 µg/m³, p < .001). During the three-week period, there were 188 STEMI patients admitted for PCI during the lockdown versus an average 254 STEMI patients before the lockdown period (incidence rate ratio = 0.74, p = .001). Reperfusion strategy was predominantly primary PCI in both time periods (96% versus 95%). However, there was a significant delay in treatment during the lockdown period, with more late presentations (>12 h after onset of pain) (14% versus 7.6%, p = .04) and with longer door-to-balloon times (median of 45 versus 39 min, p = .02). Although the in-hospital mortality between the two periods was comparable (5.9% versus 6.7%), 5 of the 7 (71%) COVID-19-positive STEMI patients died. Conclusion: The present study revealed a 26% reduction in STEMI admissions and a delay in treatment of STEMI patients. Less exposure to external STEMI triggers (such as ambient air pollution) and/or reluctance to seek medical care are possible explanations of this observation.